Multiple Tophaceous Gout of Hand with Extensor Tendon Rupture - Haruki Tobimatsu; Masanori Nakayama; Yu Sakuma; Hitoshi Imamura; Koichiro Yano; Hiroko Itagaki; Katsunori Ikari (Case Reports in Orthopedics)
A 45-year-old man presented with painless subcutaneous masses bilaterally on his hands and loss of motion or contracture of the fingers. Initially, drug therapy to reduce the serum uric acid was administered and was expected to reduce the tophi. However, during observation at the clinic, spontaneous rupture of an extensor tendon occurred, and surgical repair of the tendon and resection of the masses were performed. Surgical exploration of the right hand showed hypertrophic white-colored crystal deposits that both surrounded and invaded the extensor digitorum communis of the index finger, which was ruptured. Histopathologic examination of the specimen demonstrated findings consistent with gouty tophi. Tophaceous gout can induce a rupture of tendons during clinical observation, and surgical resection of the tophi might be needed to prevent ruptures.